THE POWER OF LETTING GO : HOW TO DROP EVERTHING THAT'S HOLDING YOU BACK - Purkiss, John (London : ASTER, an imprint of Octopus Publishing Group, 2020)
When you let go, you live intuitively. Everything flows, because you are no longer attached to things being a certain way, to being a certain person or always being right. What a relief. The irony is that when you feel stuck in any area of your life - career, relationships, purpose, health or money - letting go can seem very hard. You cling on for dear life just at the moment you need to take the leap. In The Power of Letting Go, John Purkiss explains why we should let go and how we can do it, using proven techniques to make things happen.
Keywords: Self-actualization (Psychology).